2016
DOI: 10.1002/jor.23176
|View full text |Cite
|
Sign up to set email alerts
|

Femoral epiphyseal cartilage matrix changes at predilection sites of equine osteochondrosis: Quantitative MRI, second‐harmonic microscopy, and histological findings

Abstract: Osteochondrosis is an ischemic chondronecrosis of epiphyseal growth cartilage that results in focal failure of endochondral ossification and osteochondritis dissecans at specific sites in the epiphyses of humans and animals, including horses. The upstream events leading to the focal ischemia remain unknown. The epiphyseal growth cartilage matrix is composed of proteoglycan and collagen macromolecules and encases its vascular tree in canals. The matrix undergoes major dynamic changes in early life that could we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 45 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…The degenerating cartilage canal vessels and occasional adjacent areas of necrotic cartilage are typical findings, and are interpreted as either normal loss of cartilage canals that occurs during development, or early osteochondrosis lesions. Interestingly, the fissures or cartilage canals seen were most frequently seen in the distal scapula, and not in the typical joints where osteochondrosis lesions develop, or where lesions were seen in treated foals [3,[14][15][16]. Superficial and deep erosions were only seen in the foals treated with enrofloxacin post-partum.…”
Section: Discussionmentioning
confidence: 99%
“…The degenerating cartilage canal vessels and occasional adjacent areas of necrotic cartilage are typical findings, and are interpreted as either normal loss of cartilage canals that occurs during development, or early osteochondrosis lesions. Interestingly, the fissures or cartilage canals seen were most frequently seen in the distal scapula, and not in the typical joints where osteochondrosis lesions develop, or where lesions were seen in treated foals [3,[14][15][16]. Superficial and deep erosions were only seen in the foals treated with enrofloxacin post-partum.…”
Section: Discussionmentioning
confidence: 99%
“…There has recently been a plethora of experimental imaging investigations with a goal to detect early osteochondrosis lesions in foals and pigs including CT (both clinical [9] and micro-CT [10]) and MRI (quantitative [11][12][13] and susceptibility-weighted imaging [14][15][16][17]). However, although advancing knowledge of early lesions and their morphology, these methods are not widely available or economically practical for screening purposes at the farm.…”
Section: Introductionmentioning
confidence: 99%
“…For a clinical application of these results, future studies should correlate SHG with MRI and test whether the findings of changes in the matrix integrity can be translated and detected using an in vivo imaging method. Chondronecrosis was shown previously to be visible using MRI, and areas in cartilage with reduced SHG intensity were associated with increased T2 relaxation time . If translation is possible, a longitudinal study could test whether change in matrix integrity is a predictor of progression to OCD.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, due to the cross‐sectional nature of this study, one cannot exclude the possibility that the differences in the SHG intensity between normal and necrotic matrix existed prior to ischemic necrosis. A recent study demonstrated that the SHG intensity in normal equine growth cartilage varies in different regions, and it was speculated that the risk of vascular failure could be higher in areas with weaker SHG intensity. However, this observation fails to explain why the matrix changes in the current study were focal and confined to the necrotic areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation